Ecotourism-Based Learning Models in Efforts to Implement Effective Learning: A conceptual research - Budiyanto, Moch. Agus Krisno; Hadi, Samsun; Aminah, Tien; Husamah, H. (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2020)
Various previous studies have shown that ecotourism has great potential and benefits when associated with education and especially in learning. This review study aimed to explore an ecotourism-based learning model at the high school level in Malang, East Java. The focused in the review were (1) competencies and indicators of learning outcomes of all subjects in all subjects that could apply ecotourism-based learning 2) the potential for regional ecotourism (especially school environments in East Java) which could be used for ecotourism-based learning based on competencies and outcome indicators learning, and 3) drafted recommendations for learning models based on ecotourism. Based on the results of a review of various references, it can be stated that four things need to be considered in the application of an ecotourism-based learning model, namely the conceptual framework, planning, implementation, evaluation, and furthering the ecotourism-based learning model. Furthermore, It was necessary to develop an ecotourism-based Learning Model that follows an appropriate development model, so that an implementable model is produced.